2007
DOI: 10.1111/j.1442-9071.2006.01409.x
|View full text |Cite
|
Sign up to set email alerts
|

Ropivacaine versus lidocaine for deep‐topical, nerve‐block anaesthesia in cataract surgery: a double‐blind randomized clinical trial

Abstract: Deep-topical anaesthesia with ropivacaine and lidocaine in cataract surgery is safe and the two anaesthetic agents do not present differences in the degree of analgesia achieved. Deep-topical anaesthesia with ropivacaine or lidocaine was equally effective in providing anaesthesia with sufficient quality for cataract surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…Based on the VAS scores, the patients who underwent deep topical anesthesia reported less pain. This is similar to the results of Martini et al who reported a lower pain score in patients receiving topical ropivacaine with respect to topical lidocaine, although their results did not reach statistical significance [18], whereas Ugur et al did not report any significant difference in pain score when comparing deep topical anesthesia with ropivacaine to deep topical anesthesia with lidocaine [26]. Similar to the results of Ugur [26], surgeon satisfaction was good in both groups, but in our study this was better in the deep topical anesthesia group.…”
Section: Discussionsupporting
confidence: 87%
“…Based on the VAS scores, the patients who underwent deep topical anesthesia reported less pain. This is similar to the results of Martini et al who reported a lower pain score in patients receiving topical ropivacaine with respect to topical lidocaine, although their results did not reach statistical significance [18], whereas Ugur et al did not report any significant difference in pain score when comparing deep topical anesthesia with ropivacaine to deep topical anesthesia with lidocaine [26]. Similar to the results of Ugur [26], surgeon satisfaction was good in both groups, but in our study this was better in the deep topical anesthesia group.…”
Section: Discussionsupporting
confidence: 87%